Ø¨ÙØ¹ Ø§ÙØªÙØ³ÙØ· ÙÙ Ø§ÙÙÙÙ Ø§ÙØ¥Ø³ÙØ§ÙÙ - Muqorobin, Ahmad (DINIKA : Academic Journal of Islamic Studies, 2016)
Installment purchase occurred and often widely circulated around society in this era, because societyâs necessity directly in good whereas the payment transaction cannot be settled at the same time, just like buying house, motorcycle, refrigerator, etc. The buyers sometimes cannot buy those goods for cash in the concept of this transaction has a consequence that installment price is higher than the cash price, because of addition price on deferred payment. This trading product has unknown yet by the society, especially in Muslim community. Muslim community hesitates about how is the law of this trading: some people said it is prohibited because consist of riba (usury), while others said allowed (halal). Based on the phenomenon above, this paper will discuss on the installment purchase according to fiqh which based on Islamic Sharia clearly and truly, by explaining the prepositions (dalil), condition, and ethics for both buyers and sellers, and also explaining the excess and the deficiencies of it. By the purpose to avoid the hesitancy and piece of the self-confidence, so we can do buying and selling transaction in accordance to the Sharia principles. This paper is literature study with normative approach to achieve the have way purposed. The writer collects the primary and secondary data source by the observation and documentation rules. Afterward, writher analyzing those data with inductive method which is based on the special principles and arranged in general formulation and deductive method in order to take the conclusion which explaining by descriptive and critical analysis.Â Keywords: Trading, Economy, Fiqhu al-Islamy Â